Advances in Cancer Treatment by Targeting the Neddylation Pathway - Gai, Wenbin; Peng, Zhiqiang; Liu, Cui Hua; Zhang, Lingqiang; Jiang, Hong (Frontiers in Cell and Developmental Biology, 2021)
Developmental down-regulation protein 8 (NEDD8), expressed by neural progenitors, is a ubiquitin-like protein that conjugates to and regulates the biological function of its substrates. The main target of NEDD8 is cullin-RING E3 ligases. Upregulation of the neddylation pathway is closely associated with the progression of various tumors, and MLN4924, which inhibits NEDD8-activating enzyme (NAE), is a promising new antitumor compound for combination therapy. Here, we summarize the latest progress in anticancer strategies targeting the neddylation pathway and their combined applications, providing a theoretical reference for developing antitumor drugs and combination therapies.